1979
DOI: 10.1115/1.3450944
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Thermally-Induced Flow Oscillations in Supercritical Helium

Abstract: The density wave stability boundary has been experimentally determined for super critical helium flowing in a long (L = 185 m), heated channel of high aspect ratio (L/d = 46 (10)4). A pressure drop ratio and the fluid expansion ratio correlate the oscillation inception point data. The growth of enthalpy (temperature) perturbations in a heated channel has been experimentally verified. During the density wave oscillation, the channel exit temperature and inlet mass flow were observed to be in phase, and the osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Another very interesting investigation was carried out by Daney et al [145]. In this work, DWO II are studied in a long test section (L/D = 46000) using supercritical helium as working fluid to simulate superconducting power-transmission lines.…”
Section: Density-wave Instabilitiesmentioning
confidence: 99%
“…Another very interesting investigation was carried out by Daney et al [145]. In this work, DWO II are studied in a long test section (L/D = 46000) using supercritical helium as working fluid to simulate superconducting power-transmission lines.…”
Section: Density-wave Instabilitiesmentioning
confidence: 99%
“…Daney et al (1979) performed an experimental study of supercritical helium flowing in a heated channel and reported density-wave type of flow oscillations. Analytical results were not given, but formulations were derived to support the understanding presented.…”
Section: Introductionmentioning
confidence: 99%
“…In normal gravity, thermally induced oscillations have been observed in a variety of cryogenic systems [1]. In some applications, unstable density could cause large temperature oscillations that can be destructive, for example, in a superconducting power transmission system when transition temperatures for superconductors are reached [2].…”
Section: Introductionmentioning
confidence: 99%